Kinetics of Photocatalyzed Reactions: Five Lessons Learned - Ollis, David F. (Frontiers in Chemistry, 2018)
Elucidation of kinetics of photocatalyzed chemical mechanisms occurring at interfaces (gas-solid, liquid-solid) has been challenging. We summarize here five lessons learned over five decades. 1. An assumed reaction network leads to a single kinetic model, but a common model, the Langmuir-Hinshelwood rate equation, r = kcat K C/ [1 +KC ], arises from multiple mechanisms, hence models alone do not reveal unique mechanisms. 2. The Langmuir-Hinshelwood model parameter kcat represents the slow step at a catalyst surface, and, in thermal catalysis, depends upon the reactant structure. However, early photocatalysis work with light chlorinated hydrocarbons in aqueous solutions showed a single kcat value, independent of reactant structure. 3. The dependence of the Langmuir-Hinshelwood parameters, kcat and K, upon intensity indicates that a pseudo-steady state approach is more fundamental than the presumed equilibrated adsorption of the LH model. 4. Dyes and phenols are commonly studied, and claimed as first order reactions, despite often exhibiting rate constants which diminish with increasing contaminant concentration. We show that such studies are the result of intrinsic zero order data plotted on a semilog graph, and involve zero order rate limitation by reactant saturation, oxygen mass transfer, or light supply. 5. The apparent kinetics for contaminant removal from photocatalytic self-cleaning surfaces depends upon multiple circumstances, including the geometry of reactant deposit, catalyst porosity, and reactant light absorption. A single decision table suffices to indicate the apparent reaction order, n, to assume when fitting photocatalytic kinetic data from self-cleaning surfaces to a power law rate form, rate = k Cn.